TINJAUAN YURIDIS PENYELESAIAN SENGKETA LIMA DESA ANTARA KABUPATEN KAMPAR DENGAN KABUPETEN ROKAN HULU - Pratama, Angga; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
One corollary of the doctrine of territorial decentralization in particularbore the tiered system of government, which in the context of the system ofadministration commonly known in Indonesia with the central government(central government) and local government (local government). In the context ofthe Unitary Republic of Indonesia (Republic of Indonesia) the establishment oflocal government is a process that has been, is and will be ongoing. Done throughthe formation of regional expansion, the region that gave birth to the process ofexpansion of new regional governments although philosophically intended toconduct regional arrangement, in fact also leaves many issues one of them aborder dispute between Kampar regency with Rokan Hulu is related that fivevillage , village of Muara Intan, Intan Jaya, Rambah Samo, Tanah Datar, RimbaJaya, and Rimba Makmur. The occurrence of the border dispute between theKampar Regency of Rokan Hulu certainly cause a lot of problems in society, onethat is fundamental to the uncertainty yuridisdiksi disputed territory, then thepublic administrative services, community identity and political rights of thepeople. Of course it should look for a solution see already so many rules thatestablish the village setatus five. therefore the purpose of this thesis, namely; FirstLegal Aspects of Settlement between Kampar Regency Village Five with RokanHulu. The second implication of Juridical five disputed village on theimplementation of the Government.This type of research is classified in this type of normative research,because in this peneletian authors conducted a study of the principles of law andlegal systematics. While the source of the data used is using secondary data. Datacollection techniques in this study the authors use the method of assessmentliterature or documentary studies.From the research problem, there are two main things that inferred. Thefirst aspect of the legal dispute between Kampar five village with Rokan Hulu related closely with the region of Constitutional Law relating to AdministrativeLaw Second Border Dispute implications for the implementation of obscurity.Advice Writers, First Minister of the Interior to immediately execute the SupremeCourt Decision No. 395 K/TUN/2011 as respect for the rule of law. Both theGovernment of Kampar and Rokan Hulu district in order to promote the interestsof the five village communities in the village liam menyelesaiakan dispute. Third,as an ideal law, the future of dispute resolution required an integrated border.Keywords:-Dispute- Resolution-Boundary- Region